Physician perspectives on placebo ethics - Bliamptis, John (Journal of medical ethics, 2022)
Clinical use of placebos is controversial among bioethicists. While placebos have been shown to provide benefit for patients with some conditions, offering placebos to patients without disclosing that they are placebos raises ethical concerns, including the concern that this lack of transparency about the nature of placebos amounts to deceiving patients. Some have proposed open-label placebos (OLPs) as an ethically preferable alternative: patients are offered placebos and told that the treatment being offered is a placebo. To contribute to the ongoing discussion about the ethics and feasibility of clinical use of placebos, we conducted focus groups to explore physician attitudes about clinical use of placebos, including non-disclosed and OLPs, and physician attitudes about the underlying ethical issues. We found that while the non-transparency and deceptiveness of offering non-disclosed placebos was a concern for some physicians, their primary focus when considering both non-disclosed and OLPs was identifying and weighing potential harms and benefits to patients. Some participants also felt further research and training in prescribing OLPs would be needed before they would be willing to use them in their practice.